2007
DOI: 10.1007/s00213-007-0954-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific visuomotor deficits due to alcohol intoxication: Evidence from the pro- and antisaccade paradigms

Abstract: The saccade latency data strongly suggest that alcohol intoxication impairs temporal aspects of saccade generation, irrespective of the level of processing triggering the saccade. The absence of effects on anti-saccade errors calls for further research into the notion of alcohol-induced impairment of the ability to inhibit prepotent responses. Furthermore, the specific impairment of saccade amplitude in the anti-saccade task under alcohol suggests that higher level processes involved in the spatial remapping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 48 publications
9
36
1
4
Order By: Relevance
“…As compared to placebo, low-dose lorazepam (1-2 mg) significantly increases saccade latency and decreases peak velocity (Masson et al 2000). Similar effects can be seen after consumption of moderate amounts of ethanol (Vorstius et al 2008). In addition, specific and marked impairment of saccadic eye movements have been reported in early Alzheimer's (Yang et al 2012), mild frontotemporal dementia (Boxer et al 2006), and in post concussion syndrome (Heitger et al 2008).…”
Section: Introductionsupporting
confidence: 56%
“…As compared to placebo, low-dose lorazepam (1-2 mg) significantly increases saccade latency and decreases peak velocity (Masson et al 2000). Similar effects can be seen after consumption of moderate amounts of ethanol (Vorstius et al 2008). In addition, specific and marked impairment of saccadic eye movements have been reported in early Alzheimer's (Yang et al 2012), mild frontotemporal dementia (Boxer et al 2006), and in post concussion syndrome (Heitger et al 2008).…”
Section: Introductionsupporting
confidence: 56%
“…Interest in this paradigm surged after the discovery that frontal lobe lesions specifically and severely affect human performance of antisaccades, while prosaccades (i.e., saccades directed to the visual stimulus) are facilitated [3]. Vorstius et al [168] showed that the saccade latency data strongly suggest that alcohol intoxication impairs temporal aspects of saccade generation, irrespective of the level of processing triggering the saccade. Furthermore, the specific impairment of saccade amplitude in the anti-saccade task under alcohol suggests that higher level processes involved in the spatial remapping of target location in the absence of a visually specified saccade goal are specifically affected by alcohol intoxication.…”
Section: Antisaccade Paradigmmentioning
confidence: 99%
“…This is broadly consistent with some previous reports of acute effects of alcohol on saccadic inhibitory control tasks. For example, more studies report a lack of alcohol effect or even a positive alcohol effect on anti-saccade task performance (Blekher et al, 2002;Khan et al, 2003;Vassallo et al, 2002;Vorstius et al, 2008) than report an impairment (Crevits et al, 2000;Marinkovic et al, 2013). Nonetheless, studies considering the effect of alcohol on the delayed ocular response task find significant effects of alcohol on premature saccades (e.g., Abroms et al, 2006;Weafer and Fillmore, 2012).…”
Section: Alcohol Does Not Affect Saccadic Ssrtmentioning
confidence: 99%
“…Participants make either a reflexive saccade to a target location (pro-saccade) or a saccade to the opposite location (anti-saccade) inhibiting their reflexive response. While two studies found alcohol to increase anti-saccade error rates in either head-injured participants (Crevits et al, 2000; blood alcohol levels between 1.89 and 3.84 g/l) or healthy participants (Marinkovic et al, 2013; alcohol dose 0.6 g/kg for males and 0.55 g/kg for females), two studies found no effect (healthy participants, Blekher et al, 2002; breath alcohol concentration 80 mg/dl; Vorstius et al, 2008; breath alcohol concentration 65 mg/dl). Counter-intuitively, two studies even found decreases in error rates (healthy participants, Khan et al, 2003; blood alcohol concentration 0.08%; Vassallo et al, 2002; blood alcohol concentration 0.044%), which may be due to alcohol attenuating the reflexive response rather than the inhibitory control process (Fillmore and Weafer, 2013).…”
Section: Introductionmentioning
confidence: 98%